Workshop Latihan Kematangan Mental Bagi Pelatih dan Mahasiswa Olahraga di Kabupaten Kebumen dan Sukabumi - Erick Burhaein et.al (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2023)
Mental maturity is very important in the world of sports, especially for athletes. Athletes who have mental maturity tend to be better able to maintain concentration and focus during training and competition. This service activity aims to carry out mental maturity training workshops for coaches and sports students in Kebumen and Sukabumi regencies. The results of the workshop showed that there was interest in the theme in terms of participants from the large number of participants in both districts, namely a total of 73 participants. Participants from various professions or jobs include researchers, lecturers, students, and teachers who have interests. Workshop participants participated in this activity to upgrade science in the study of mental maturity training in athletes. This activity has implications in terms of providing knowledge related to mental maturity training in athletes which will be implemented by participants through independent and sustainability activities. Suggestions for future activities with other materials and may focus on specific athletes such as early age, disability, or elite athletes. Focus and in-depth studies are also tailored to the knowledge needs of trainers in the field.